Evaluating the strength and deformation characteristics of a soil bag pile from full-scale laboratory tests. Issue 6 (1st December 2006) - Tatsuoka, F.; Aqil, U.; Lohani, T. N.; Mohri, Y.; Matsushima, K.
Abstract : The compressive strength of a soil bag pile when compressed vertically and the shear strength when sheared laterally were evaluated by performing a series of full-scale loading tests. The effects of soil bag material, backfill soil type, number of soil bags in a pile and associated effects of the end restraint at the top and bottom ends of a soil bag pile were evaluated. The results of vertical compression tests showed that initial compaction of the backfill in the soil bags is effective in increasing the initial stiffness at small deformation, and that preloading is even more effective in increasing the overall stiffness and decreasing the creep deformation. The shear strength of a soil bag pile subjected to lateral shear is substantially smaller as compared with a high compressive strength when compressed vertically. It was found that the shear strength of well-graded granular backfill was partially mobilised in vertical compression tests but the mobilisation was even lower in the lateral shear tests. The soil bag pile showed highly anisotropic strength characteristics, resulting from no or negligible complementary shear stresses acting at the vertical interface between the horizontally adjacent soil bags and highly anisotropic reinforcing effects of geosynthetic cover sheets of soil bags.